2014
DOI: 10.1007/s11999-014-3484-2
|View full text |Cite
|
Sign up to set email alerts
|

Does a Microprocessor-controlled Prosthetic Knee Affect Stair Ascent Strategies in Persons With Transfemoral Amputation?

Abstract: Background Stair ascent can be difficult for individuals with transfemoral amputation because of the loss of knee function. Most individuals with transfemoral amputation use either a step-to-step (nonreciprocal, advancing one stair at a time) or skip-step strategy (nonreciprocal, advancing two stairs at a time), rather than a step-over-step (reciprocal) strategy, because step-to-step and skip-step allow the leading intact limb to do the majority of work. A new microprocessor-controlled knee (Ottobock X2 1 ) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Another study assessed stair ascent using the Ottobock X2 MPK compared with NMPKs [29]. The X2 and Genium are comparable regarding stair gait function, using flexion/extension resistance timing to maximize user climbing ability with their own strength as opposed to systems offering external-powered assistance [8,[29][30]. Persons with TFA used a reciprocal stepping strategy with the X2, necessitating greater hip power, corroborating Bellman et al's findings [8,29].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Another study assessed stair ascent using the Ottobock X2 MPK compared with NMPKs [29]. The X2 and Genium are comparable regarding stair gait function, using flexion/extension resistance timing to maximize user climbing ability with their own strength as opposed to systems offering external-powered assistance [8,[29][30]. Persons with TFA used a reciprocal stepping strategy with the X2, necessitating greater hip power, corroborating Bellman et al's findings [8,29].…”
Section: Discussionmentioning
confidence: 53%
“…Specific research regarding functional stair gait performance and stair gait during load carriage is necessary to corroborate Bellman et al's findings. Another study assessed stair ascent using the Ottobock X2 MPK compared with NMPKs [29]. The X2 and Genium are comparable regarding stair gait function, using flexion/extension resistance timing to maximize user climbing ability with their own strength as opposed to systems offering external-powered assistance [8,[29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldridge Whitehead et al studied stair ascent in young active male TFAs [14], reporting that the majority of participants (13 of 14) preferred a ST or skip-step (an ST gait that advances two stairs per stride) gait on their conventional prostheses, which were a C-Leg or Total Knee (Ossur), and that the majority (10 of 14) preferred a SOS gait while using the Genium knee. While the adoption rate of the SOS as the preferred gait style was not as high in our study, we did observe a more heterogeneous representation of the amputee population, and our participants were asked to not use handrails during testing.…”
Section: Discussionmentioning
confidence: 99%
“…Aldridge et al [25] observed that 71% of subjects were capable of ascending stairs step over step in a population of 14 subjects with MCFL rating 3 and 4. Highsmith et al [26] reported that 14 out of 20 (70%) K3 and K4 transfemoral amputees who received training were able to ascend stairs reciprocally.…”
Section: Discussionmentioning
confidence: 99%